Analisis Pengaruh Angkatan, Gender, dan Prestasi Terhadap Kemampuan Membaca Pembuktian Mahasiswa Pendidikan Matematika - Nabila Zahida; Mohamad Waluyo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aimed to examine the effect on the generation, gender, and performance to the reading comprehension in mathemathics. The statical method used is multiple regression. The test results indicate that there is significant influence of generation and performance on the reading comprehension; there is no direct influence of gender on the reading comprehension.